BIOANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF OXACEPROL IN HUMAN PLASMA BY USING UV-VISIBLE SPECTROPHOTOMETER - Sri, K. Bhavya; Banu, Shaheen; Sumakanth, Mogili (Journal of Global Pharma Technology, 2024)
Osteoarthritis is commonly treated with oxaceprol. An easy, quick, accurate, and exact technique for estimating oxaceprol is required since 1 billion people worldwide suffer from rheumatoid arthritis each year. Utilizing a UV-visible spectrophotometer, procedures are developed and then validated. Only a few techniques for estimating oxaceprol have been described, but after reviewing the literature, we developed a method with a wide linearity range and low DL and QL values. Methanol: ACN was used as the solvent in the development of this procedure. The chosen wavelength for examination in this approach was discovered to be 215nm. To do the spectrum study, a double beam spectrophotometer with UV and visible light was employed.In the UV spectrophotometer, the absorbance of several series of dilutions was measured at a wavelength of 215 nm. Oxaceprol concentration was plotted on x-axis & absorbance was taken on y-axis to plot Calibration curve. All the validation parameters were validated as per ICHQ2 (R1) guidelines. Keywords: Osteoarthritis, UV-visible spectrophotometer, linearity, calibration curve, methanol.